tan e
cot 0
+
1- cot 0 1 - tan 0
= 1 + sec 0 coseco
[Hint : Write the expression in terms of sin 0 and cos 0]
Answers
Answered by
0
Answer:
Step-by-step explanation:
sin (1+tan)+cos (1+cot)=sec+cosec
=> LHS= sin (1+tan)+cos (1+1/tan)
=> sin (1+tan)+cos (1+tan)/tan
=> (1+tan)(sin+cos/tan)
=> (1+tan)(sin.tan+cos)/tan
=> (1+tan)(sin^2/cos+cos)/tan
=> (1+tan)(sin^2+cos^2)/tan.cos
=>(1+tan)/tan.cos
=>(1/tan.cos)+tan/tan.cos
=>( cot/cos)+(1/cos)
=> cosec +sec
LHS= RHS.
Like my answer and brainlist if you find it useful!
Similar questions
Chemistry,
2 months ago
Math,
2 months ago
Math,
6 months ago
Accountancy,
11 months ago
Chemistry,
11 months ago
Social Sciences,
11 months ago